2023
DOI: 10.1007/s00221-023-06644-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of sense of body ownership but not agency during virtual tool-use training is associated with an altered body schema

Abstract: In this study we examined if training with a virtual tool in augmented reality (AR) affects the emergence of ownership and agency over the tool and whether this relates to changes in body schema (BS). 34 young adults learned controlling a virtual gripper to grasp a virtual object. In the visuo-tactile (VT) but not the vision-only (V) condition, vibro-tactile feedback was applied to the palm, thumb and index fingers through a CyberTouch II glove when the tool touched the object. Changes in the forearm BS were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…Results indicated that VT Feedback was more effective leading to a reduction in gripper size on average. Further results revealed that PE was significantly lower (more negative, indicating more reduction in gripper size) for the VT than for the V Feedback condition (for review; Jahanian Najafabadi, Küster, Putze & Godde, 2023a). In a second study in OA, we found a similar performance level as in YA during training Blocks.…”
Section: How Does the Practice Effect Vary With Sensory Feedback Cond...supporting
confidence: 54%
“…Results indicated that VT Feedback was more effective leading to a reduction in gripper size on average. Further results revealed that PE was significantly lower (more negative, indicating more reduction in gripper size) for the VT than for the V Feedback condition (for review; Jahanian Najafabadi, Küster, Putze & Godde, 2023a). In a second study in OA, we found a similar performance level as in YA during training Blocks.…”
Section: How Does the Practice Effect Vary With Sensory Feedback Cond...supporting
confidence: 54%